QURUQLIK MOLLYUSKALARINING EKOLOGIK GURUHLARI SHAKLLANISHIDA TASHQI MUHIT OMILLARINING O‘RNI - Karimkulov, A.T; Nabijonova , O.G‘ (Actual problems and prospects of the study of the fauna, 2024)
The article describes the influence of external environmental factors on the formation of various ecological groups of terrestrial molluscs. According to the information presented in the literature, land molluscs form 8 ecological groups according to their nutrition. According to the level of soil moisture and distribution of molluscs in relation to water bodies, they form 3 ecological groups.